BENTHIC FAUNA IN THE VICINITY OF BALLENY ISLANDS (Collected Abstracts of Transactions of the Tokyo University of Fisheries No. 5,March 1982) - MURANO, Masaaki; INOUE, Kiyoshi; MARUYAMA, Takashi (1982)
P(論文) departmental bulletin paper